Outcomes of postoperative delirium in patients undergoing cardiac surgery: A systematic review and meta-analysis - Lin, Lingyu; Zhang, Xuecui; Xu, Shurong; Peng, Yanchun; Li, Sailan; Huang, Xizhen; Chen, Liangwan; Lin, Yanjuan (Frontiers in Cardiovascular Medicine, 2022)
Background: Postoperative delirium (POD) is an acute brain dysfunction that is frequently observed in patients undergoing cardiac surgery. Increasing evidence indicates POD is related to higher mortality among cardiac surgical patients, but the results remain controversial. Moreover, a quantitative evaluation of the influence of POD on hospital days, intensive care unit (ICU) time, and mechanical ventilation (MV) time has not been performed. Objective: This study aimed to evaluate the correlation between POD and outcomes in patients undergoing cardiac surgery by a systematic review and meta-analysis. Methods: A total of 7 electronic databases (Cochrane Library, PubMed, EMBASE, CINAHL Complete, MEDLINE, Wan-fang database, and China National Knowledge Infrastructure) were searched from January 1980 to July 20, 2021, with language restrictions to English and Chinese, to estimate the impact of the POD on outcome in patients who underwent cardiac surgery. The meta-analysis was registered with PROSPERO (Registration: CRD42021228767). Results: Forty-two eligible studies with 19785 patients were identified. 3368 (17.0%) patients were in the delirium group and 16417 (83%) were in the non-delirium group. The meta-analysis showed that compared to patients without POD, patients with POD had 2.77-fold higher mortality (OR=2.77, 95%CI 1.86-4.11, P<0.001), 5.70-fold higher MV (>24h) rate (OR= 5.70, 95%CI 2.93-11.09, P<0.001); and longer MV time (SMD=0.83, 95%CI 0.57-1.09, P<0.001), ICU time (SMD=0.91, 95%CI 0.60-1.22, P<0.001), hospital days (SMD=0.62, 95%CI 0.48-0.76, P<0.001). Conclusions: The synthesized evidence suggests that POD is causally related to the increased risk of mortality, prolonged length of ICU and hospital stay, and a longer duration of MV time. Future research should focus on the interventions for POD, to reduce the incidence.